Anaphylaxis to levetiracetam in an adolescent: a very rare occurence - Kahraman, Şeyma; Değermenci, Şeyda; Oktay, Mehmet Ali; Menderes, Deniz; Güleryüz, Okşan Derinöz; Arhan, Ebru; Bakırtaş, Arzu; Ertoy-Karagöl, Hacer İlbilge (The Turkish Journal of Pediatrics, 2021)
Background. Antiepileptic drugs (AEDs) are among the most common causes of severe delayed-type hypersensitivity reactions such as Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and Drug Reaction with Eosinophilia and Systemic Symptoms(DRESS) in children. These reactions are more commonly seen with aromatic AEDs such as phenytoin and carbamazepine than the non-aromatic or new generation AEDs. However immediate-type hypersensitivity reactions such as urticaria/angioedema, anaphylaxis are very rare with AEDs. Case. Levetiracetam is an increasingly used new non-aromatic antiepileptic drug and reported to have a better safety profile in daily practice. We present the first adolescent case who developed an anaphylactic reaction with intravenous levetiracetam, not reported in this age group before in the literature. Conclusion. Hypersensitivity reactions in the form of anaphylaxis can be rarely observed with new generation AEDs. Therefore, when any antiepileptic drug is started on any patient, immediate type serious reactions such as anaphylaxis should be kept in mind, not only focusing on delayed reactions such as SJS, TEN,or DRESS.